Health disparities across income and the business cycle - Hildur Margrét Jóhannsdóttir 1994- (2016)
We examine how business cycles affect income-related distribution of diseases and health disorders. By using data from a survey conducted by the Directorate of Health in Iceland in 2007, 2009 and 2012 we aim at examining how the prevalence of thirty diseases and health conditions is distributed across the income spectrum. Furthermore, we take advantage of the unusually sharp changes in economic conditions in Iceland during the Great Recession initiated in 2008 and the partial recovery that had already taken place by 2012 to analyze how income-related health inequality changed across the different time periods. The concentration curve and the concentration index are calculated for each disease, both overall and by gender. In all cases, we find a considerable income-related health inequality favoring higher income individuals, with a slight increase over the study period. Between 2007 and 2009, our results indicate increased inequality for women but decreased inequality for men. Between 2009 and 2012 on the contrary, men’s inequality increases but women’s decreases. The overarching result is thus that the economic hardship of the crisis temporarily increased female income-related health inequality, but decreased that of men.